The relationship between supply chain management practices, performance measurement practices and firm performance: An empirical study of the practices in Tanzania’s industrial sector / Frank Augustine Elisha Mkumbo - Frank Augustine , Elisha Mkumbo (2008)
Supply chain management is considered by many firms as the best competitive strategy option in the prevailing turbulent and dynamic business environment that has resulted from effects of globalization. Despite being acknowledged as the best option in overcoming the effects of globalization in business, supply chain management has come with multiple challenges in its implementation that include the development of trust among supply chain members, process alignment and integration, to mention a few. Even with these challenges, a supply chain is expected to function as one entity, thus it has to be monitored in its performance. The assessment of the success of organizations throughout history has been performed using performance metrics. Performance measurement quantifies effectiveness and efficiency of action using metrics. The proper selection of key performance variables allows for major consideration in improvement, problem identification, and gauging performance against plans, norms, or best practices, and gives directions for improvement plans. Performance measurement and metrics pertaining to supply chain management have not received adequate attention from researchers or practitioners. This two stage sequential mixed method applied research explores the nature, transformation, and, processes of supply chain management and performance measurement practices in the industrial sector of Tanzania. The primary data is collected using a mail questionnaire from 264 industrial firms in Tanzania; the analysis is performed using the AMOS program for structural equation modeling (SEM) techniques. A performance index, developed from the quantitative analysis results, is used to identify the four firms for the case study. The results of the analysis (both survey and case study) show that supply chain management is practical in Tanzania and improves the performance of organizations in the supply chains. The practice is observed to be in its infancy in the study firms. Performance measurement practices, pertaining to supply chains, are observed to be less practiced, though they show a positive impact on the performance. Many firms use only financial measures and performance measurement systems. Better performance is observed in firms that embrace supply chain management and appropriate performance measurement practices. Time based performance is found to mediate the impacts of supply chain management and performance measurement practices to overall firm performance.